2015
DOI: 10.1590/2359-3997000000027
|View full text |Cite
|
Sign up to set email alerts
|

The thyroid hormone receptor β-selective agonist GC-1 does not affect tolerance to exercise in hypothyroid rats

Abstract: Objective: Investigate the effect of GC-1 on tolerance to exercise in rats with experimental hypothyroidism. Materials and methods: Hypothyroidism was induced with methimazole sodium and perchlorate treatment. Six groups with eight animals were studied: control group (C), hypothyroid group without treatment (HYPO); hypothyroidism treated with physiological doses of tetraiodothyronine (T 4 ) or 10 times higher (10×T 4 ); hypothyroidism treated with equal molar doses of GC-1 (GC-1) or 10 times higher (10×GC-1). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…12 The water temperature was maintained at 32 ± 2°C to be thermally neutral in relation to the rats' body temperature. 13,14 Physical training was carried out for four weeks, with three swimming sessions per week. To increase the workload, a small vest with lead weights was placed around the anterior region of the trunk.…”
Section: Physical Training Protocolmentioning
confidence: 99%
“…12 The water temperature was maintained at 32 ± 2°C to be thermally neutral in relation to the rats' body temperature. 13,14 Physical training was carried out for four weeks, with three swimming sessions per week. To increase the workload, a small vest with lead weights was placed around the anterior region of the trunk.…”
Section: Physical Training Protocolmentioning
confidence: 99%
“…In line, Kannisto and co-workers recently showed that GC-1 is able to reduce atherosclerosis, defined as cholesterol content in the arterial wall, in aortas of ApoE-deficient mice [ 11 ]. Moreover, in a recent study, it has been shown that unlike 3,5,3′5′-tetraiodothyronine (T 4 ), GC-1 did not influence tolerance to physical exercise in hypothyroid rats [ 28 ]. This is of importance since both hypothyroidism as well as hyperthyroidism itself are associated with exercise intolerance [ 29 ].…”
Section: Thyroid Hormone Receptor Beta Agonistsmentioning
confidence: 99%
“…GC-24 is a TRβ receptor agonist with similar affinity for TRβ to TRα, but with a much higher selectivity. This increased selectivity (~40-fold for TRβ over TRα) was reached by the addition of a phenyl group at the 3′ position of the distal aryl ring of GC-1 [ 28 ] and the subsequent creation of a new hydrophobic cluster [ 27 ]. GC-24, in contrast to GC-1, has shown to have no activity in the brain, which has been suggested to be caused by a limited entry through the blood-brain barrier [ 30 ].…”
Section: Thyroid Hormone Receptor Beta Agonistsmentioning
confidence: 99%
“…[7][8][9] The treatment of hypothyroidism is hormone replacement which usually should be continued throughout the whole life. 10,11 On the other hand, treatment with thyroid hormones can increase the risk of osteoporosis and fracture risk. One of the modalities that are used for inducing the bone repair is laser therapy.…”
Section: Introductionmentioning
confidence: 99%